The Influence of Promotion and Service Quality on Customers' Decisions to Save at PT Bank Rakyat Indonesia (Persero) Tbk Medan Gatot Subroto Branch - Karo-Karo, Perlaban; Ginting, Margono; Tarigan, Hendri Mayanta; Siagian, Riduan; Pratami, Eggi Indriani; Saragih, Jayati Taruli (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to see the influence of promotion and service quality on customers' decisions to save at Bank Rakyat Indonesia (Persero) Tbk Medan Gatot Subroto Branch, both partially and simultaneously at Bank Rakyat Indonesia (Persero) Tbk Medan Gatot Subroto Branch. The type of research used is quantitative. This research uses two independent variables, namely promotion and service quality with one dependent variable, namely the customer's decision to save. The population in this research is Bank Rakyat Indonesia (Persero) Tbk Medan Gatot Subroto Branch customers, totaling 100 customers determined the sample size in this research by making the population a sample so that the sample for this research is 50 respondents. The data source for this research is primary data using a research instrument in the form of a questionnaire. The data collection method used is survey research. Promotions influence customers' savings decisions. Promotion and service quality together influence customers' savings decisions. The service quality variable has a significant influence on customers' decisions to save at BRI Bank Medan Gatot Subroto Branch, having at value of 2.537 with a significance of 0.014. Then the value in the distribution table (0.025) is 2.011. So the calculated t value is 2.537 > t table 2.011, which means that Ha is accepted and H0 is rejected so that the service quality variable has a significant influence.